Gorillas In The Mist - Apted, Michael; Brown, Bryan, 1947-; Constantin Alexandrov; Iain Cuthbertson; John Omirah Miluwi; Julie Harris; Waigwa Wachira; Sigourney Weaver (USA Guber-Peters Company, 1988)
Sigourney Weaver stars as Dian Fossey, in this true story about Fossey's study of gorillas, and her efforts to stop the decimation of the endangered apes.
The story of Dian Fossey, a scientist who came to Africa to study the vanishing mountain gorillas, and later fought to protect them.
Harold T.P. Hayes
Languages : English, German, Spanish Subtitles : English, Dutch, Arabic, Bulgarian, Czech, Danish, Finnish, Hebrew,Greek, Hungarian,Icelandic, Norwegian, Polish,Swedish
Keywords: Drama